Chest CT for Non-Radiologists A Practical Guide - Salvatore, Mary M. (Springer International Publishing, 2018)
This book is a practical guide to chest CTs for non-radiologists. A succinct and focused book, Chest CT for Non-Radiologists is designed to give the reader just the level of information they need to know. Chapters begin with the basics of a chest CT, including when they are necessary and the basic procedures, so physicians and medical professionals can best counsel their patients. The book then moves into various parts of the chest and the common diseases and presentations that would be found in a chest CT (lung fibrosis, pulmonary nodules, etc.). It teaches the reader what to look for and how to provide the most accurate and effective diagnosis for their patients. There are also several de-identified CT scans that allow the reader to test his or her skills. This is an ideal resource for non-radiologist physicians -- including pulmonologists, internal medicine physicians, emergency medicine physicians, and critical care specialists, residents, and medical students -- to learn the basics of the chest CT and thereby provide optimal care for their patients. .